Problem bezrobocia na wrocławskim obszarze metropolitalnym - wybrane aspekty - Potoczna, Iwona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The unemployment belongs to the most significant social problems of the modern world. This phenomenon is widely considered to cause many negative after-effects. The scale of threat of this problem in the Wroclaw Metropolitan Area - the region situated in the south-west macroregion in Poland - is spatially diverse. For the sake of the fact that major part of Lower Silesia region is threatened by the structural unemployment, the goal of the article is to search for the diagnosis for the chosen aspects which concern the actual situation in the labour market of the Wroclaw Metropolitan Area. The article presents reasons of the unemployment that occurred in the examined region at such a high level. Information taken into account in the analysis describes the unemployed people registered in the Work Office according to their age, education, sex and job seniority. There are factors appointed that cause problems to pile up in the Lower Silesia and the reaction of people loosing their job. The statistical data come from year books issued by Central Statistical Office between 1999 and 2004. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 301-308